Cerebellar cortical neuron responses evoked from the spinal border cell tract - Geborek, Pontus; Spanne, Anton; Bengtsson, Fredrik; Jörntell, Henrik (Frontiers in Neural Circuits, 2013)
Spinocerebellar systems are likely to be crucial for cerebellar hallmark functions such as coordination. However, in terms of cerebellar functional analyses, these are perhaps among the least explored systems. The aim of the present study is to achieve activation of a single component of the spinocerebellar systems and to explore to what extent it can influence the spike output of granule cells, Golgi cells, molecular layer (ML) interneurons (stellate and basket cells) and Purkinje cells (PCs). For this purpose, we took advantage of a unique arrangement discovered in neuroanatomical studies, in which the spinal border cell (SBC) component of the ventral spinocerebellar system was found to be the only spinocerebellar tract which ascends in the contralateral lateral funiculus (coLF) and have terminations in sublobulus C1 of the paramedian lobule in the posterior cerebellum. Using electrical stimulation of this tract, we find a subset of the cerebellar cortical neurons in this region to be moderately or powerfully activated. For example, some of our granule cells displayed high intensity responses whereas the majority of the granule cells displayed no response at all. The finding that more than half of the PCs were activated by stimulation of the SBC tract indicated that this system is capable of directly influencing cerebellar cortical output. The implications of these findings for the view of the integrative functions of the cerebellar cortex are discussed.